2019
DOI: 10.5194/hess-23-3335-2019
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of hydrological ensemble prediction in forecasting floods and its components over the Yarlung Zangbo River basin, China

Abstract: Abstract. In recent year, floods becomes a serious issue in the Tibetan Plateau (TP) due to climate change. Many studies have shown that ensemble flood forecasting based on numerical weather predictions can provide an early warning with extended lead time. However, the role of hydrological ensemble prediction in forecasting flood volume and its components over the Yarlung Zangbo River (YZR) basin, China, has not been investigated. This study adopts the variable infiltration capacity (VIC) model to forecast the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 87 publications
2
12
0
Order By: Relevance
“…Apart from criteria that are used to calculate model errors over the entire test period, there are also many criteria that focus on a certain period of interest. For example, the criteria mentioned above are calculated over flood periods (Liu et al, 2017(Liu et al, , 2019 or dry periods (Demirel et al, 2013). There have also been studies that calibrated hydrological models via hydrological components other than the streamflow, such as evapotranspiration (Pan et al, 2017), soil moisture (Gao et al, 2015), the snow water equivalent, and even glacier melt (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from criteria that are used to calculate model errors over the entire test period, there are also many criteria that focus on a certain period of interest. For example, the criteria mentioned above are calculated over flood periods (Liu et al, 2017(Liu et al, , 2019 or dry periods (Demirel et al, 2013). There have also been studies that calibrated hydrological models via hydrological components other than the streamflow, such as evapotranspiration (Pan et al, 2017), soil moisture (Gao et al, 2015), the snow water equivalent, and even glacier melt (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the criteria mentioned above are calculated over flood periods (Liu et al, 2017(Liu et al, , 2019 or dry periods (Demirel et al, 2013). There have also been studies that calibrated hydrological models via hydrological components other than the streamflow, such as evapotranspiration (Pan et al, 2017), soil moisture (Gao et al, 2015), the snow water equivalent, and even glacier melt (Liu et al, 2019). Another approach that is applied to improve the performance of models is the use of hydrological signatures (Shafii and Tolson, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulating in those data‐sparse basins remains a challenge and should be careful. Previous studies (Zhang et al ., 2013; Tong et al ., 2014a; Liu et al ., 2019) have proved that streamflow simulation in the TP is usually subject to underestimation. Therefore, seeking more accurate meteorological proxy to complement insufficient in situ measurements is crucial in this region.…”
Section: Introductionmentioning
confidence: 99%
“…This region is also one of the most sensitive areas to global climate change due to the particularly cold and high‐elevation environment (Liu and Chen, 2000; Yao et al ., 2012). It is found that in the past decades the TP has undergone prominent changes in hydrological processes as a result of global warming (Wang et al ., 2014; Wang et al ., 2017; Liu et al ., 2019), making it urgent to establish accurate modelling system to track and predict those changes.…”
Section: Introductionmentioning
confidence: 99%